Ultrasound quantification of knee meniscal extrusion: the potential of weight-bearing and dynamic evaluations. A systematic review - Giuseppe Martinese; Fabio Tortorella; Luca Andriolo; Giancarlo Facchini; Marco Miceli; Giuseppe Filardo (EFORT Open Reviews)
Purpose: Meniscal extrusion (ME) can have detrimental effects. The aim of this study was to analyze the evidence about the reliability, potential of standing and dynamic evaluations, and influencing factors identified by using ultrasound (US) to evaluate knee ME. Methods: A systematic review of the literature was performed in February 2024 on PubMed, Scopus, and the Cochrane Library databases to select all articles, dealing with the US evaluation of ME. Relevant data of the involved articles, including study type, number of patients, age, sex, US technique, and data comparison with other radiological examinations, were extracted and collected for the study analysis. Results: Sixty studies on 4,742 patients were included: 38 cross-sectional, ten longitudinal, two case–control, and ten biomechanical studies. A strong correlation was found between MRI and US, with good US sensitivity (96%) and specificity (82%), and moderate to excellent interrater and intrarater reliability. US examinations in the standing position with weight-bearing or more complex dynamic conditions reported a significant influence of weight-bearing on MME. US was able to identify a relationship between meniscus posterior root tear and MME, as well as between ME and both pain and early osteoarthritis. Conclusions: US is a valuable tool for the study of ME and the identification of the association between ME and various conditions. US in dynamic and weight-bearing evaluations is useful to characterize this anatomical abnormality in different pathologies, including OA, meniscal lesions, and in the follow-up of surgical procedures, providing important data to choose the best treatment to address patients affected by ME.